URBAN INFORMAL SETTLEMENTS: THE CRITICAL ROLE OF WOMEN IN THE RESILIENCE TO CLIMATE CHANGE AND ADAPTATION IN HOPLEY, ZIMBABWE (Proceedings of the International Conference on Future of Women, 2025)
The susceptibility to the effects of climate change is intensified by the disparity andexclusion associated with geographical location, ethnic background, gender, poverty, and othereconomic and social determinants. This qualitative study investigated the living conditions of theurban poor in informal settlements of Hopley, Zimbabwe and illustrate how the appropriation ofprivate, parochial, and public spaces by female residents of Hopley informal settlement affects theirability to manage climatic risks. Informal settlements are characterized by substandard dwellings orshanties constructed in violation of formal laws and regulations. The informal community of Hopleydo not have access to clean potable water or sufficient infrastructure for public health, drainage, andessential services. This paper examined strategies for developing resistance to the impacts of climatechange by women in informal communities such as Hopley. The research offers valuable insights onthe varying degrees of women's participation in climate resilience development, based on acomprehensive analysis of existing literature and in depth interviews of 12 women living in Hopley.It additionally examined the measures being taken to tackle climate resilience in informalsettlements, specifically, initiatives sponsored by the local community to improve settlements andstrengthen their capacity to endure the effects of climate change and support marginalizedpopulations. Furthermore, the study explored strategies for overcoming obstacles to achieving largerscale and effectiveness, such as using synergies with the Sustainable Development Goals.
Keywords: climate change; informal settlement; resilience; poverty; sustainable development goals